The roles and molecular mechanisms of long non-coding RNA WT1-AS in the maintenance and development of gastric cancer stem cells - Xiaobei Zhang; Meng Jin; Shiqi Liu; Mingde Zang; Lei Hu; Tao Du; Baogui Zhang (Heliyon, 2023)
It has been proposed that cancer stem cells (CSCs) are responsible for almost all malignant phenotypes of tumors. Long non-coding RNA WT1 antisense RNA (WT1-AS) has been found to be implicated in lung cancer cell stemness. However, the roles and molecular mechanisms of WT1-AS in the development of gastric cancer stem cells (GCSCs) remain unknown. Our present study showed that WT1-AS negatively regulated WT1 expression in GCSCs. WT1-AS knockdown or Wilms’ tumor 1 (WT1) overexpression improved GCSC proliferative and migratory capacities, inhibited GCSC apoptosis, potentiated the resistance of GCSCs to 5-FU, promoted GCSC EMT, induced HUVEC angiogenesis, enhanced GCSC stemness, and facilitated in-vitro 3D GCSC aggregate formation. WT1-AS overexpression exerted reverse effects. WT1-AS ameliorated the malignant phenotypes of GCSCs by down-regulating WT1 in vitro. WT1-AS inhibited tumor growth and metastasis, and reduced tumor stemness in GCSCs-derived (s.c., i.p., and i.v.) xenografts in vivo. Moreover, XBP1 was identified as an upstream regulator of WT1-AS in GCSCs. Also, 4 potential WT1-AS downstream targets (i.e. PSPH, GSTO2, FYN, and PHGDH) in GCSCs were identified. Additionally, CACNA2D1 was demonstrated to be a downstream target of the WT1-AS/WT axis. XBP1 or CACNA2D1 knockdown exerted an adverse effect on the maintenance of stem cell-like behaviors and characteristics of GCSCs. In conclusion, WT1-AS weakened the stem cell-like behaviors and characteristics of GCSCs in vitro and in vivo by down-regulating WT1. Investigations into the molecular mechanisms underlying the complex phenotypes of GCSCs might contribute to the better management of gastric cancer.